Impact of Positional Isomerism on Pathway Complexity in Aqueous Media. Issue 14 (3rd February 2020) - Helmers, Ingo; Shen, Bowen; Kartha, Kalathil K.; Albuquerque, Rodrigo Q.; Lee, Myongsoo; Fernández, Gustavo
Abstract: Pathway complexity has become an important topic in recent years due to its relevance in the optimization of molecular assembly processes, which typically require precise sample preparation protocols. Alternatively, competing aggregation pathways can be controlled by molecular design, which primarily rely on geometrical changes of the building blocks. However, understanding how to control pathway complexity by molecular design remains elusive and new approaches are needed. Herein, we exploit positional isomerism as a new molecular design strategy for pathway control in aqueous self‐assembly. We compare the self‐assembly of two carboxyl‐functionalized amphiphilic BODIPY dyes that solely differ in the relative position of functional groups. Placement of the carboxyl group at the 2‐position enables efficient pairwise H‐bonding interactions into a single thermodynamic species, whereas meso ‐substitution induces pathway complexity due to competing hydrophobic and hydrogen bonding interactions. Our results show the importance of positional engineering for pathway control in aqueous self‐assembly. Abstract : A matter of position : Rational placement of functional groups for weak interactions has been exploited as a new method for pathway control in aqueous self‐assembly. The results may contribute to understanding the molecular design principles that govern the outcome of self‐assembly processes in water.